Endoscopicretrieval of Gastric Foreign Bodies in Two Dogs - Atmakur Venkatesh; D.Sumathi; K. Mohanambal; R.Ravi; Kesari Raghu Ram Reddy; K.K. Ponnu Swamy (The Indian Veterinary Journal, 2025)
Gastric and esophagealforeign bodies (FBs) can cause vomiting, decreased appetite, discomfort due to abdominal pain and lethargy in dogs. These are presented as life-threateningemergencies and need immediate intervention. In this study, two dogs of varying breeds and ages with a history of foreign body ingestion and vomiting were examined through radiography, ultrasonography and endoscopy. Radiography helped to identify and localizeone of the two foreign bodies reported in this study. However, gastro-endoscopy provided direct visualization of both the foreign bodies and allowed for their retrieval under general anesthesia in these cases.